Crude fibre digestion in broiler and indigenous Venda chickens - Ginindza, Muzi Mandla (My University, 2020)
A study was conducted to determine the effect of dietary crude (CF) levels of (3, 4, 5 and 7 %) on feed intake, digestibility, growth rate, feed conversion ratio (FCR) and live weight of male Ross 308 broiler and indigenous Venda chickens aged 1 to 42 days. The study, also, determined the effect of dietary CF level on the gastrointestinal morphology and digesta pH of gut organs of male Ross 308 broiler and indigenous Venda chickens aged 42 days. Dietary CF levels affected (P<0.05) feed intake, growth rate and live weight of male Ross 308 broiler and Venda chickens aged 1 to 21 days. A dietary CF level of 3.9 % optimized feed intake, while 4.5 % dietary CF optimized growth rate and live weight in male Ross 308 broiler chickens. However, dietary CF levels of 4.4, 4.8, 5.9 and 4.7 % optimized feed intake, growth rate, FCR and live weight, respectively, of male Venda chickens aged 1 to 21 days. Therefore, dietary CF level for optimal productivity depended on the breed of the chicken and production parameter of interest. Higher dietary CF levels decreased (P<0.05) crude protein (CP), neutral detergent fibre (NDF) and acid detergent fibre (ADF) digestibility values in male Ross 308 broiler chickens. Dietary CF levels of 3.8, 3.7 and 4.1 % optimized dry matter (DM) digestibility, metabolizable energy (ME) intake and nitrogen retention, respectively, in male Ross 308 broiler chickens aged 14 to 21 days. Increased dietary CF level, also, decreased (P<0.05) NDF and ADF digestibility values in male Venda chickens aged 14 to 21 days. Dry matter and CP digestibility values, ME intake and nitrogen retention of Venda chickens were optimized at dietary CF levels of 3.5, 3.7, 3.3 and 4.1 %, respectively. Feed intake of male Ross 308 broiler chickens aged 22 to 42 days were affected (P<0.05) by dietary CF level; and it was optimized at a dietary CF level of 6.4 %. Increased dietary CF level resulted in poorer growth rate, FCR and live weight of male Ross 308 broiler chickens. However, dietary CF levels of 4.5, 5.8, 6.4 and 5.7 %, optimized feed intake, growth rate, FCR and live weight, respectively, of male Venda chickens aged 22 to 42 days. Dietary CF levels of 3.4, 4.4, 3.7 and 4.4 %, optimized DM, CP and NDF digestibility values, and nitrogen retention, respectively, in male Ross 308 broiler chickens. However, dietary CF levels of 5.1, 5.3, 4.9, 10.1 and 5.1 % optimized DM, CP, NDF and ADF digestibility values, and nitrogen retention, respectively, of male Venda chickens. Therefore, dietary CF level for v optimal response in the chickens depended on breed, age and production variable of interest. The GIT weight of male Ross 308 broiler chickens was optimized at a dietary CF level of 4.1 %. In increased dietary CF level in male Ross 308 broiler chickens increased gizzard weights and decreased small intestine weights (P<0.05). Dietary CF levels of 6.3, 5.9 and 8.0 % optimized GIT, gizzard and caecum weights, respectively, in male Venda chickens. The small intestine weight of male Venda chickens was not affected (P<0.05) by dietary CF level. Caecum weight of male Venda chickens increased (P<0.05) with higher dietary CF level. However, caecum weights of male Ross 308 broiler chickens were not affected (P>0.05) by dietary CF level. The GIT and small intestine lengths were affected (P<0.05) by dietary CF level in male Ross 308 broiler chickens. Dietary CF levels of 5.6 and 5.5 % optimized GIT and small intestine lengths, respectively. However, in male Venda chickens, GIT and small intestine lengths were not affected (P>0.05) by dietary CF level. Digesta pH of the proventriculus and gizzard were affected (P<0.05) by dietary CF level in male Ross 308 broiler and Venda chickens. Different dietary CF levels of 5.5 and 7.4 % optimized the proventriculus and gizzard digesta pH in male Ross 308 broiler chickens, respectively. However, dietary CF levels of 4.2 and 4.3 % optimized the proventriculus and gizzard digesta pH values, respectively, in male Venda chickens. The two breeds of chickens had similar digesta pH values of the crop, proventriculus, gizzard and large intestines. However, male Venda chickens had higher (P<0.05) small intestine digesta pH values than male Ross 308 broiler chickens aged 42 days. Caecum digesta pH values of Ross 308 broiler chickens were higher (P<0.05) than those of Venda chickens aged 42 days. The second study was conducted to determine the effect of sodium bicarbonate supplementation level in the drinking water on feed intake, digestibility, FCR, growth rate, gut organ weight, length and digesta pH of male Ross 308 broiler and Venda chickens aged 22 to 42 days. The study, also, determined the effect of sodium bicarbonate supplementation level in drinking water on types of bacterial species in crop and gizzard digesta, as well as its effect on meat quality of male Ross 308 broiler and indigenous Venda chickens. Increased sodium bicarbonate vi supplementation level increased (P<0.05) water pH. Supplementation levels of 8.9, 2.04, 2.97 and 2.97 g of sodium bicarbonate per litre of drinking water optimized water intake, feed intake, growth rate and live weight of male Ross 308 broiler chickens, respectively. In male Venda chickens, there was a strong and positive relationship between sodium bicarbonate supplementation level and water intake of Venda chickens. A single supplementation level of 3.8 g of sodium bicarbonate per litre of drinking water optimized growth and live weight of male Venda chickens. There was a negative relationship between sodium bicarbonate supplementation level in the drinking water and NDF digestibility of male Ross 308 broiler chickens. Supplementation levels of 2.63, 6.67 and 7.0 g of sodium bicarbonate per litre of drinking water optimized DM and CP digestibility values, and nitrogen retention, respectively, in male Ross 308 broiler chickens. However, supplementation levels of 3.2 and 4.52 g of sodium bicarbonate per litre of drinking water optimized DM and NDF digestibility values, respectively, in male Venda chickens. There were negative relationships between sodium bicarbonate supplementation level in the drinking water and CP digestibility and nitrogen retention of male Venda chickens. Supplementation levels of 5.7, 2.2, 3.8, 7.6 and 7.2 g of sodium bicarbonate per litre of drinking water optimized proventriculus, gizzard and small intestinal weights, and GIT and small intestines lengths, respectively, in male Ross 308 broiler chickens. However, a sodium bicarbonate supplementation level of 2.8 % optimized proventriculus weights of male Venda chickens; the other digestive organ weights and lengths of Venda chickens were not affected (P>0.05) by sodium bicarbonate supplementation level. Sodium bicarbonate supplementation in the drinking water affected bacterial species found in the crops and gizzards of the chickens. There were different bacterial species found in the crop and gizzard digesta of male Ross 308 broiler and Venda chickens. Meat colour (L*, a* and b*) of the breasts and thighs of both breeds of chickens were not affected (P>0.05) by sodium bicarbonate supplementation. However, the redness (a*) values of the breast meat of male indigenous Venda chickens were higher (P<0.05) than those of breast meat from male Ross 308 broiler chickens. Sodium bicarbonate supplementation level did not affect (P>0.05) breast meat tenderness, juiciness, flavour and overall acceptability values and meat pH of Ross 308 broiler chickens. Supplementation levels of 3.6, 3.2 and 4.7 g of vii sodium bicarbonate per litre of drinking water optimized meat juiciness, flavour and shear force of male Venda chickens, respectively. It was concluded that sodium bicarbonate supplementation in the drinking water affected growth, NDF digestibility and bacterial species composition of male Ross and Venda chickens. Sodium bicarbonate supplementation level for optimal response in chickens depended on the breed and production variables of interest.
Thesis (Ph. D. (Animal Production)) -- University of Limpopo, 2020
Keywords: Fibre digestion; Broiler; Venda chickens; Poultry -- Feeding and feeds; Poultry -- Breeding; Broilers (Chickens) -- Productivity